2018
DOI: 10.5755/j01.ee.29.1.19247
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Work Arrangements from Generation and Gender Perspectives: Evidence from Lithuania

Abstract: The demand for employee-oriented and individualized work arrangements and practices that permit temporal and spatial flexibility in work processes and help to fit changing personal needs and environmental conditions is constantly increasing. A growing number of private companies and public organizations are adopting flexible work arrangements (FWAs) to help employees balance their work-family demands, and companies cope with variations in demand, reduce expenses, and be more attractive for employees. Employees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…Today's workforce actively seeks out the opportunity to work more flexibly and the provision and the usage of FWAs are increasing rapidly (Regus, 2017). Flexible work arrangements can be defined as formal or informal arrangements, which allow employees some flexibility and choice to control and readjust their working hours and/or spatial location of work (Campbell, 2015;Ciarniene & Vienazindiene, 2018).…”
Section: Literature Review the Rise And Prevalence Of Flexible Work Arrangementsmentioning
confidence: 99%
“…Today's workforce actively seeks out the opportunity to work more flexibly and the provision and the usage of FWAs are increasing rapidly (Regus, 2017). Flexible work arrangements can be defined as formal or informal arrangements, which allow employees some flexibility and choice to control and readjust their working hours and/or spatial location of work (Campbell, 2015;Ciarniene & Vienazindiene, 2018).…”
Section: Literature Review the Rise And Prevalence Of Flexible Work Arrangementsmentioning
confidence: 99%
“…Organizations have also promoted an evolution of the balance between professional life and personal life toward an integration of these two domains, because the generations in the current labour market demanded so (Ciarniene & Vienazindiene, 2018;Sanchez-Hernandez et al, 2019). It is necessary to consider the differences between these, as each of these generations express different values and needs in the same challenging and mutable world.…”
Section: Discussionmentioning
confidence: 99%
“…According to Pew Research Centre (Fry, 2015), majority of workforce today are Millennials. Analysis of different generations has revealed that Millennials are highly satisfied with the flexible work arrangements (Ciarniene and Vienazindiene, 2018). Millennials have associated various benefits with flexible work arrangements including improved efficiency, reduced stress, positive impact on health etc.…”
Section: Indian Context Of Diversitymentioning
confidence: 99%